Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/cssc.201901885
|View full text |Cite
|
Sign up to set email alerts
|

Resource‐Saving Production of Dialdehyde Cellulose: Optimization of the Process at High Pulp Consistency

Abstract: Oxidation of cellulose with periodate under aqueous conditions yields dialdehyde cellulose, a promising functional cellulose derivative. The main obstacles for this oxidation have been its slow kinetics and the dilute reaction conditions, requiring considerable amounts of water and energy. In this study, these drawbacks are overcome by conducting the oxidation at high cellulosic pulp consistency with a cellulose/water weight ratio of 1:4. The oxidizer, cellulose, and water are efficiently mixed in a ball mill.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…The hydroxylamine hydrochloride reacts with aldehyde group to generate hydrochloric acid. The aldehyde content of oxidized DAC can be determined by sodium hydroxide titration of the released hydrochloric acid [22].…”
Section: Determination Of the Aldehyde Content By Titration Methodsmentioning
confidence: 99%
“…The hydroxylamine hydrochloride reacts with aldehyde group to generate hydrochloric acid. The aldehyde content of oxidized DAC can be determined by sodium hydroxide titration of the released hydrochloric acid [22].…”
Section: Determination Of the Aldehyde Content By Titration Methodsmentioning
confidence: 99%
“… 269 Recently, it was shown that the resource efficiency of the periodate oxidation can be tremendously increased by reaction at high solid content. 207 In the case of cellulose, these oxidized groups can be postmodified to give access to CNF decorated with various functional groups, including, among others, carboxylate and sulfonate ones. 270 , 271 Sulfated polysaccharides can be made using sulfur trioxide pyridine, yielding a polysaccharide substituted with sulfate groups ( Figure 4 C).…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Chemical modifications is very significant as it enhances the cellulose adsorption capacity and the ability for removing heavy metals from aqueous media Chemical modification of cellulose maybe done by using acids, organic compounds, bases or minerals. [27][28][29]. The oxidation of the cellulose by a selective oxidizing agent like periodate is very important as the resultant dialdehyde cellulose has great ability to be modified with many functional groups as aliphatic or aromatic amines.…”
Section: Introductionmentioning
confidence: 99%